Internal Control System, Whistleblowing System, Organizational Commitment And Fraud Prevention: Individual Morality As A Moderating Variable : MORALITAS INDIVIDU SEBAGAI VARIABEL MODERASI - Dinda Dwiyanti; Agung Prasetyo Nugroho Wicaksono; Ihyaul Ulum (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
The purpose of this study is to examine the effect of the internal control system, whistleblowing system, and organizational commitment to fraud through individual morality as moderation. This research is associative descriptive research. The population used is all permanent employees of Bank BNI Tulungagung with a sampling form of convenience sampling set by the researcher as many as 55 respondents. The analysis method of this research is PLS analysis through SEM approach by utilizing SmartPLS 3.0 software. The results showed that the internal control system had a significant effect on fraud prevention. However, the whistleblowing system and organizational commitment do not affect fraud prevention. Individual morality weakens the relationship of the internal control system to fraud prevention.